Assessment of circulatory adjustments during underwater apnoea in elite divers by means of a portable device. (14th September 2012) - Tocco, F.; Marongiu, E.; Pinna, M.; Roberto, S.; Pusceddu, M.; Angius, L.; Migliaccio, G.; Milia, R.; Concu, A.; Crisafulli, A.
Abstract: Aim: Considering that sympathetic activation is induced by exercise, it is reasonable to assume that hemodynamic adjustments to exercise act in opposition to those elicited by the diving response. However, cardiovascular measurements have never been performed during underwater dynamic apnoea (DA), and this hypothesis remains speculative. Methods: Data concerning heart rate (HR), stroke volume (SV) and cardiac output (CO) during static apnoea (SA) and DA were collected from 12 elite divers by means of an impedance cardiograph adapted to the underwater environment. Mean arterial pressure (MBP), systemic vascular resistance (SVR) and arterial oxygen saturation (SaO2 ) were also assessed. Five trials were performed by the divers: head‐out immersion during normal breathing (test A); 3 min of SA immersed at the surface (B) and at 3 m depth (C); DA till exhaustion immersed at the surface (D) and at 3 m depth (E). Results: Both B and C conditions led to bradycardia (−17%) compared to A and also induced a decrement in SV (−8%) and in CO (−25%), while MBP was maintained because of an increase in SVR. A significant MBP increment (+11%) was detected only during tests D and E, when a SaO2 drop was also present, whereas HR, SV and CO remained unchanged. Conclusion: We concluded that typical diving response was present only during SA, while sympathetic activation was induced by exercise during DA, which partially obscured the effects of the diving response.